An Analysis of Code Mixing Used by Beauty Influencers in Tiktok - Moethya Aslim; Eliwarti Eliwarti; Hadriana Hadriana (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
The aims of this study were to analyze the types of code mixing used by beauty influencers in TikTok and the reasons of why they used code mixing in their videos. The method that used in this research is descriptive qualitative to collect the data from the transcript of beauty influencers’ videos. Interviewing the beauty influencers is used to find out the reasons of why they use code mixing in their videos through Instagram’s DMs. The writer selected three beauty influencers in TikTok as the sample of this research. After analyzing 21 videos from beauty influencers, the result of this research found that 954 utterances of code mixing which appeared in the transcript from beauty influencers’ videos. From that, there were three types of code mixing based on Hoffman’s theory as follows; intra-sentential code mixing, intra-lexical code mixing and involving change of pronunciation. Meanwhile, there was only one reason of why the beauty influencers used code mixing in their videos, that was because of habit.